Practical Training Report in Kota Setar District Office / Nurul Naslina Abdullah - Abdullah, Nurul Naslina (University Technology MARA Sarawak, 2017)
Kota Setar are being named after a tree. A lot of setar trees grows across a land named Kota Bukit Pinang. Sultan Muhammad Jiwa Zainal Abiddin was the first king who found the place and built up the kingdom. Sultan Muhammad Jiwa ordered his peoples to explore a new government area to replace Kota Bukit Pinang while having a break at Kota Bukit Pinang. After that, peoples are being ordered to build up a lot of canal for agriculture purposes, avoidance from flash flood and also for communication purposes. Not only that, the excess soil will be used to build a castle. The canals will connect few main road likes Alor Semadom to the main river at the Pumpong. From there, peoples can sell their agricultures products to the near villages such as Kanchut, Pengkalan Badak and also Gerbang or also known as Gedebang. On 31st December 1735, Sultan Muhammad Jiwa Zainal Abiddin officially start his government at the Istana Kota Setar.